Attack Density and Distribution of Dendroctonus micans (Kugelann) in Standing and Felled Oriental Spruce Trees - Özcan, Gonca Ece; Alkan Akinci, Hazan; Eroğlu, Mahmut (Kastamonu University, 2016)
The aim of this study is to investigate attack density and distribution of Dendroctonus micans (Kugelann) (Coleoptera: Curculionidae) in standing and felled oriental spruce, Picea orientalis (L.) Link., trees.  For this purpose, a total of 179 standing and 38 felled trees were evaluated. D. micans attacks largely concentrated in the initial several meters of the boles and particularly in the initial 1 m part of both tree groups. 62.53% and 67.22% of EHs in the initial 2 m of boles of standing and felled trees, respectively were counted in the initial 1 meter. In felled trees, the ratios of entrance holes per meter up to the initial 9 m of boles were similar to each other (%7.02-9.24), other than the significant difference in the initial 1 meter (18.96%). Above nine meters, the ratio of entrance holes per meter of boles varied in the range of 0.54% to 3.64%. In the case of standing trees, unsuccessful entrances comprised 23.40% of the total entrances. In the case of felled trees, approximately one in every four entrance holes in the bole section up to the initial 8 m was unsuccessful, as similar to standing trees, whereas one in every three EHs in upper sections was unsuccessful.
Keywords: 2. Zero hunger; 15. Life on land